Relationship between interproximal caries and using bitewing radiographs in patient older than twenty - Goodarzipur D; Karami P (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: Caries and bone loss are the most common diseases in oral cavity. The prevalence of these diseases will be reduced by controlling their risk factors. In this study, bitewing radiographs of patients were examined to illustrate the relationship between caries and bone loss."nMaterials and Methods: One-hundred and fifty bitewing radiographs of 86 patients were evaluated. In these radiographs, caries and distance between alveolar crest and CEJ were measured. In addition, confounding variables (contact type, tooth type, tooth surface) were assessed. Furthermore, patients were asked about the use of other possible risk factors of bone loss like smoking, brushing, and flossing. The data were analyzed using Regression analysis."nResults: Findings of this study showed that the relationship between caries and bone loss was significant (P=0.02). Also, there were significant relationships between flossing (P=0.03), tooth type (P=0.0001) tooth surface (P=0.02) and bone loss. Finally the multivariate analyses considering confounding variables illustrate significant relationship between caries and bone loss (P=0.0001)."nConclusion: Caries and bone loss have important roles as the risk factors for each other. Thus, it is necessary to prevent these risk factors and treat them as soon as possible to reduce these diseases.